Asset administration shell submodel for wireless communication system. Issue 2 (2022) - Cainelli, Gustavo P.; Underberg, Lisa; Rauchhaupt, Lutz; Pereira, Carlos E.
Abstract: In Industry 4.0 the production system must be adapted to the needs of customers, without planning every detail in advance. Therefore also the communication system can not be planned and installed for the worst case. If changes are necessary, the communication system must be adapted automatically. This work proposes to model relevant elements of communication systems using the Asset Administration Shell which is the implementation of the Digital Twin from the Platform I4.0 perspective. This will allow negotiation between the communication system and the production system. As all the relevant information of production and communication will be in the digital domain, both systems can be adapted accordingly when it is necessary.